The society’s attitude toward 5G technologies – a case study of Poland - Ejdys, Joanna; Soler, Urszula (Technological and Economic Development of Economy, 2023)
The sustainable development of society depends, on the one hand, on the development of innovative technologies, on the other hand, on the positive and negative effects of this development. Social acceptance of new technological solutions seems to be also a key factor. One of the future technologies is 5G, which will undoubtedly have an unprecedented impact on socio-economic development. The scientific discussion on the risks caused by electromagnetic radiation in the context of a new wireless communication technology – the fifth generation (5G) standard – is going on around the world. The scientific aim of the study is to analyze the factors determining the social attitude of Poles towards 5G technology. Among the factors included are: general society attitudes of technology, the scale of actual Internet use, demographic characteristics and pro-health society attitudes. Data was collected using the CATI technique. The interviews were carried out among 1005 Polish citizens. The obtained results confirmed statistically significant relationships between the variables: attitudes towards technology (ATT) and attitudes towards 5G technology (ATT5G). Research has confirmed that people who use the Internet more frequently have more positive attitudes towards 5G technology. New knowledge regarding public attitudes toward 5G technology has been accumulated through research.